2017
DOI: 10.1167/iovs.16-20575
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ANGPT2 as a New Gene for Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy in the Chinese and Japanese Populations

Abstract: Citation: Ma L, Brelen ME, Tsujikawa M, et al. Identification of ANGPT2 as a new gene for neovascular age-related macular degeneration and polypoidal choroidal vasculopathy in the Chinese and Japanese populations. Invest Ophthalmol Vis Sci. 2017;58:107658: -108358: . DOI:10.1167 PURPOSE. We determine the angiopoietin 2 (ANGPT2) gene as a new susceptibility gene for neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV). METHODS.A total of 34 haplotype-tagging single-nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Elevated levels of ANG-2 (43 vs. 9 pg/L) were found in the aqueous humor of patients with neovascular AMD, 145 and a small study from Hong Kong has shown some suggested associations between ANG-2 SNPs and neovascular AMD, particularly polypoidal. 146 Otani et al showed that surgically excised CNV stained positive for ANG-1 and ANG-2 with increased ANG-2 immunoreactivity in the highly vascularized regions of CNV—similar to the staining pattern of VEGF. 147 Heras et al also detected variable amounts of VEGF, ANG-1, and ANG-2 in surgically excised CNV membranes; TIE-2 and VEGF receptor (VEGFR) were not detectable in their study.…”
Section: Neovascular Age-related Macular Degenerationmentioning
confidence: 81%
“…Elevated levels of ANG-2 (43 vs. 9 pg/L) were found in the aqueous humor of patients with neovascular AMD, 145 and a small study from Hong Kong has shown some suggested associations between ANG-2 SNPs and neovascular AMD, particularly polypoidal. 146 Otani et al showed that surgically excised CNV stained positive for ANG-1 and ANG-2 with increased ANG-2 immunoreactivity in the highly vascularized regions of CNV—similar to the staining pattern of VEGF. 147 Heras et al also detected variable amounts of VEGF, ANG-1, and ANG-2 in surgically excised CNV membranes; TIE-2 and VEGF receptor (VEGFR) were not detectable in their study.…”
Section: Neovascular Age-related Macular Degenerationmentioning
confidence: 81%
“…Recently, a study reported that aqueous angiopoietin-like 4 (ANGPTL4) level in patients with ME due to BRVO is also significantly higher [40]. The ANGPLTL4 mediates the development of vascular permeability and angiogenesis in hypoxic conditions, is overexpressed in general ischemic retinopathy, and promotes the development of CME [41, 42]. If marked hypoxia persists, irreversible structural changes in the macular occur, and the disturbed visual acuity (VA) is almost always lasting.…”
Section: Cystoid Macular Edemamentioning
confidence: 99%
“…PCV shares many similarities with nAMD, including clinical manifestations, genetic background, and both of them are choroidal vasculopathy associated with subretinal hemorrhage, scars and fibrosis [1], so some views support PCV is a subtype of nAMD. However, they still differ in pathophysiology, histopathological, epidemiology, some clinical characteristics, treatment responses, natural course and special genes [2][3][4][5][6]. There remain controversies as to whether PCV is merely a variant of nAMD or its own distinct entity [7].…”
Section: Introductionmentioning
confidence: 99%